How should we design social protection interventions to reduce Gender-Based Violence (GBV)? - Roy, Shalini; Heinemann, Alessandra (SocialProtection.org, 2024)
There is growing interest in understanding how social protection can mitigate and prevent gender-based violence (GBV). Evidence shows that cash transfer programmes can decrease intimate partner violence (IPV), which is the most common form of GBV. Researchers have suggested various pathways through which cash transfers and other social protection programmes can affect the prevalence of GBV, highlighting specific design features that could amplify these reductions.